2018
DOI: 10.1101/312579
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Structural survey of HIV-1-neutralizing antibodies targeting Env trimer delineates epitope categories and suggests vaccine templates

Abstract: HIV-1 broadly neutralizing antibodies are desired for their therapeutic potential and as templates for vaccine design. Such antibodies target the HIV-1-envelope (Env) trimer, which is shielded from immune recognition by extraordinary glycosylation and sequence variability. Recognition by broadly neutralizing antibodies thus provides insight into how antibody can bypass these immune-evasion mechanisms. Remarkably, antibodies neutralizing >25% of HIV-1 strains have now been identified that recognize all major ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 61 publications
0
10
0
Order By: Relevance
“…Structural studies revealed two of the three amino acid positions were located at the VRC01 epitope and thus can be critical to VRC01 binding and neutralization ( Figure 1c) (12). Additionally, the top three features of bNAb 8ANC195 classifier account for a total variable importance of 48.47% and include Env residues 234 and 276, which must be glycosylated in order for 8ANC195 to bind and neutralize Env (Figure 1d, Supplementary Table S2) (13). Not all of the top discriminative features, however, involved bNAb epitope residues, suggesting that distal regions outside the epitope also affect neutralization susceptibility of HIV-1 strains ( Supplementary Table S4).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Structural studies revealed two of the three amino acid positions were located at the VRC01 epitope and thus can be critical to VRC01 binding and neutralization ( Figure 1c) (12). Additionally, the top three features of bNAb 8ANC195 classifier account for a total variable importance of 48.47% and include Env residues 234 and 276, which must be glycosylated in order for 8ANC195 to bind and neutralize Env (Figure 1d, Supplementary Table S2) (13). Not all of the top discriminative features, however, involved bNAb epitope residues, suggesting that distal regions outside the epitope also affect neutralization susceptibility of HIV-1 strains ( Supplementary Table S4).…”
Section: Resultsmentioning
confidence: 99%
“…The buried surface area between antibody and antigen was calculated using NACCESS software (12,13). The epitope and paratope residues for each antibody were defined as residues with non-zero buried surface area.…”
Section: Epitope and Paratope Buried Surface Area Calculationsmentioning
confidence: 99%
“…In particular, antibodies capable of broad neutralization of HIV have particularly high levels of SHM ( 128 , 131 , 132 ) and tend to be enriched for rare substitutions ( 104 , 133 , 134 ) (Figure 1 ). Extraordinary levels of SHM (15–35% nucleotide mutations) are characteristic of antibodies targeting HIV ( 135 ), and elevated levels of SHM have also been observed in other types of chronic infection and in systemic autoimmune disorders ( 136 ).…”
Section: Vaccine Implicationsmentioning
confidence: 99%
“…Indeed, while several recent studies in transgenic mice have elicited B cells enriched for substitutions present in the targeted mature antibody ( 144 146 ), none have yet specifically elicited critical rare substitutions or fully recapitulated the neturalization activity of the target antibodies. Notably, however, the most successful example focuses on PGT121 ( 146 ), which contains fewer rare substitutions than many other HIV antibodies ( 104 , 134 ). It may, therefore, be more prudent to choose lineage-based vaccine design targets by avoiding those with functionally important rare substitutions ( 33 , 134 ).…”
Section: Vaccine Implicationsmentioning
confidence: 99%
See 1 more Smart Citation